2006
DOI: 10.1016/j.jsgi.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Membranes From Term VAginal Deliveries Have a Zone of Weakness Exhibiting Characteristics of Apoptosis and Remodeling

Abstract: Vaginally delivered AROM FM contain a weak zone overlying the cervix. Vaginally delivered SROM FM contain a weak zone adjacent to the tear line that exhibits biochemical and mechanical characteristics suggestive of collagen remodeling and apoptosis comparable to those of the AR FM weak zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 12 publications
7
79
0
4
Order By: Relevance
“…Furthermore, regression model for biaxial dynamic test was able to explain variance significantly better than the model for biaxial static test using the same predictor variables. The fact that we confirmed that fetal membranes from term vaginal deliveries are weaker in the cervical area than those closer to the placenta, which is in accordance with previous biomechanical studies (18)(19)(20), indicates that biaxial dynamic test performed on our apparatus can successfully reproduce already established conclusions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, regression model for biaxial dynamic test was able to explain variance significantly better than the model for biaxial static test using the same predictor variables. The fact that we confirmed that fetal membranes from term vaginal deliveries are weaker in the cervical area than those closer to the placenta, which is in accordance with previous biomechanical studies (18)(19)(20), indicates that biaxial dynamic test performed on our apparatus can successfully reproduce already established conclusions.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, we were able to take only 2 samples for biaxial testing from each half of the membrane. As has been stated previously, there are biomechanical differences even between samples taken from one region (20). The level of variance explained by the regression models is somewhat low which can be attributed to inherent lack of uniformitiy in biomechanical properties of fetal membranes.…”
Section: Discussionmentioning
confidence: 61%
“…Va ginally de li ve red spon ta ne o us ROM fe tal meb ra nes con ta in a we ak zo ne ad ja cent to the te ar li ne that ex hi bits bi oc he mi cal and mec ha ni cal cha rac te ristics sug ges ti ve of col la gen re mo de ling and apop tosis com pa rab le to tho se of the ar ti fi ci al-rup tu re fe tal meb ra ne's we ak zo ne. 27 Additionally in a study con duc ted or only elec ti ve C/S pa ti ents, a discre te weak zo ne was pre sent in term pre la bor fe tal meb ra nes overl ying the cer vix, and it had bi oc hemi cal cha rac te ris tics con sis tent with tis su e re mode ling and apop to sis. 15 Anot her li mi ta ti on is the samp ling of am ni on ad ja cent to rup tu re si te which might have caused an in cre a se in the thick ness of the am ni on.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical area, often described as a "zone of extreme morphology" is the region overlying the cervix, where amnion ruptures prior to delivery. Several studies have confirmed that this region contains less epithelial cells and is significantly thinner and weaker than the rest of AM [5,6]. Physiological mechanisms involved in AM weakening in a course of gestation remain unknown [7][8][9].…”
Section: Introductionmentioning
confidence: 99%